Parametric Study of Index Properties and Compaction Characteristics of Bentonite, Kaolinite and Sand Mixtures - Jyothi D. N., Prasanna H. S., Lavanya L., B. I. Monika, Chandrashekar M. M. (International Journal of Advanced Science and Technology, 2020)
Index properties and plasticity characteristics are the two important issues related to classification and in assessing swelling characteristics of fine-grained soils. It is seldom observed that, the clay mineralogy is playing the important role in deciding the characteristics of such soils which is due to the presence of least active clay mineral like kaolinite to the most active clay mineral like montmorillonite in addition to other clay minerals like illite, etc., in different proportions. Because of physico-chemical phenomenon due to the effect of clay minerals which exhibits contradictory behaviour i.e., kaolinite exhibiting flocculent effect in relative comparison to montmorillonite having dispersion effect. The various proportions of these clay minerals is generally be ascertained by means of XRD analysis, which is generally expensive. Most of these experimental studies of fine-grained soils are region-specific. In the present experimental investigation, in order to replicate natural soils having kaolinite, montmorillonite and sand in different proportions by design mix proportions of commercially available kaolinite, bentonite and sand mixtures. A detailed experimental investigation was done to assess the physical properties and compaction characteristics subjected to various compaction energy levels like reduced standard proctor (RSP), standard proctor (SP), reduced modified proctor (RMP) and modified proctor (MP). An attempt has been made, to form a relation between the index properties of the mix proportions with the plasticity and compaction characteristics, which can be useful in preliminary designs and which are found to be cost effective. An alternative method of assessing the principle clay dominance is also presented. A new plasticity chart for the design mix proportions was also developed for classification purpose.